2020
DOI: 10.5430/jha.v9n2p22
|View full text |Cite
|
Sign up to set email alerts
|

Reporting and responding to patient safety incidents based on data from hospitals’ reporting systems: A systematic review

Abstract: Objective: This review summarizes and synthesizes the evidence on follow-up activities regarding patient safety incidents reported in hospitals.Methods: Peer-reviewed papers were retrieved with electronic searches from CINAHL, Web of Science, PubMed and Scopus databases and with manual searches in most relevant journals and in the reference lists of included studies, limiting searches to papers published in English between 2014 and 2018. A systematic review was conducted in adherence to the Preferred Reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
(186 reference statements)
0
7
0
Order By: Relevance
“…In the current study, the proportion of incidents related to medications were less reported as compared with the previously published studies. 1 13 22–24 It is noteworthy that there is no previous information on the level and reasons for medication incidents in Estonia. In the previous studies, the low level of medication-related incident reporting was explained as a lack of clear definitions of medication error, 25 26 a lack of feedback on reporting 3 8 26 and a reporter’s previous experience with such kind of incidents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the current study, the proportion of incidents related to medications were less reported as compared with the previously published studies. 1 13 22–24 It is noteworthy that there is no previous information on the level and reasons for medication incidents in Estonia. In the previous studies, the low level of medication-related incident reporting was explained as a lack of clear definitions of medication error, 25 26 a lack of feedback on reporting 3 8 26 and a reporter’s previous experience with such kind of incidents.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the WHO conceptual framework for patient safety 2 19 and previously published literature, 1 7 8 we developed a data extraction form for data collection. The extraction form was consisted of three parts.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations